Social vouchers – tool for supporting disadvantaged people / Tichetele sociale – instrument de sprijinire a persoanelor defavorizate - BALAN Aliona (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The social protection system of the population in a welfare state must be built in such a way that it quickly and efficiently adapts to changes in the standard of living of the socially vulnerable segments of the population and, at the same time, does not hinder the economic development of the country. Solving this problem requires the implementation of new social protection tools for the population, taking into account the experience of foreign countries and national characteristics. The purpose of the article is to determine the role of social vouchers in supporting disadvantaged people, identifying the characteristics and benefits of their implementation.